PERAN GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN TRANSAKSIONAL TERHADAP KETERIKATAN KERJA (STUDI PADA KARYAWAN UNIVERSITAS X) - Garvin Garvin; Willy Budiman Winata (Psibernetika, 2016)
The purpose of the study is to examine the role of transformational and transactional leadership to the employees' work engagement. Transformational leadership is defined as a leadership style that involves interaction between the leader and follower, and mutually enhance each other into higher degree of morality and motivation. Transactional leadership is defined as leadership style that occurs when the leader gives reward or discipline to the followers. Work engagement is defined as positive mental state, selffulfillment, and related to work that is characterized with vigor, dedication, and absorption. The research involves 105 employees that work in "X" University in Western Jakarta, using convenient sampling technique. Regression analysis showed that perceived transformational and transactional leadership both gives significant role to the work engagement. Keywords: transformational leadership, transactional leadership, work engagement,employee